DESAIN DAN VALIDASI VIDEO ANIMASI EKSPERIMEN KALOR DAN PERPINDAHANNYA SEBAGAI PEMANDU PRAKTIKUM DI RUMAH DALAM RANGKA MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA SMP - Izza Fauzia; Zulirfan Zulirfan; Fakhruddin Fakhruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Science is a human knowledge about nature that is obtained in a controlled way. So that students can carry out the scientific learning process, they must have an ability that scientists have in conducting scientific investigations, namely scientific process skills. The purpose of this study is to produce an animated video as a valid and practical physics practical guide at home that can train the science process skills of seventh grade junior high school students on heat and its transfer material. The research method used in this research are Research and Development (R&D) and development method with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). However, in this development research, researchers only conduct research up to the third stage, namely to the development stage. The type of data used in this study is divided into qualitative data and quantitative data. Qualitative data in the form of opinions and suggestions from the validator and quantitative data in the form of scores given by the validator on each item of the assessment of the animated video product draft along with the accompanying LKPD which was developed as a practical guide. The results of the validation at the final stage based on 5 aspects of the assessment obtained the following; the conduction practicum animation video is 3.53, the convection practicum animation video is 3.51 and the radiation practicum animation video is 3.58. The results of the validation at the final stage obtained the following averages; LKPD conduction of 3.70. The convection LKPD is 3.62 and the radiation LKPD is 3.67. So based on the description of the validation results, the media developed in the form of animated videos and practical worksheets can be declared valid. Thus, it can be concluded that the media developed by the researcher is suitable to be used as a guide for physics practicum for junior high school students at home.Keywords : Media Development, video animation, science process skills, heat and its transfer.